2015
DOI: 10.1515/aut-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Pcl/Chitosan Blended Nanofibrous Tubes Made by Dual Syringe Electrospinning

Abstract: 3D tubular scaffolds made from Poly-(Ɛ-caprolactone) (PCL)/chitosan (CS) nanofibres are very promising candidate as vascular grafts in the field of tissue engineering. In this work, the fabrication of PCL/CS-blended nanofibrous tubes with small diameters by electrospinning from separate PCL and CS solutions is studied. The influence of different CS solutions (CS/polyethylene glycol (PEO)/glacial acetic acid (AcOH), CS/trifluoroacetic acid (TFA), CS/ AcOH) on fibre formation and producibility of nanofibrous tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…These findings agreed with other reported results. Hild et al 38 prepared PCL-CS membranes with diameters ranging from 200 to 400 nm, 38 while Van der Schueren et al 11 obtained smaller PCL-CS membranes (200 to 250 nm). 11 Considering poly(ε-caprolactone)-based membranes loaded with dexamethasone (5 to 20 wt.% concerning the whole polymer content), Martins et al 30 reported nanofibers with diameters ranging from 150 nm to 1.6 µm.…”
Section: Resultsmentioning
confidence: 99%
“…These findings agreed with other reported results. Hild et al 38 prepared PCL-CS membranes with diameters ranging from 200 to 400 nm, 38 while Van der Schueren et al 11 obtained smaller PCL-CS membranes (200 to 250 nm). 11 Considering poly(ε-caprolactone)-based membranes loaded with dexamethasone (5 to 20 wt.% concerning the whole polymer content), Martins et al 30 reported nanofibers with diameters ranging from 150 nm to 1.6 µm.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 In order to benefit from the advantages of different materials in a single scaffold, electrospun composites are prepared. Many polymer blends and composites have been electrospun into a single mat using single or twin extrusion systems such as PCL/chitosan blend, 16 polycaprolactonegelatin, 17 silk fibroin-poly(ε caprolactone) blended/poly(ε caprolactone). 18 Furthermore, core-shell fibers can also be produced using the coaxial electrospinning method.…”
Section: Introductionmentioning
confidence: 99%
“…The developed composite CS–PCL scaffolds showed a faster degradation rate, more hydrophilicity, and higher thermostability, which could make them a good candidate for biomedical applications [ 24 , 25 ]. Numerous studies have shown that CS–PCL membranes are suitable and promising candidates as vascular grafts, wound dressing for the controlled release of drugs, and carriers of encapsulated enoxaparin [ 26 , 27 , 28 , 29 ]. Furthermore, recent efforts have contributed to mediating the cellular osteogenic growth peptide gene by combining amphiphilic CS, PCL, and bioglass, and gene transfection efficiency was dramatically enhanced in the experimental conditions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%